An analysis on Islamic insurance participation (Satu analisis penyertaan insurans Islam) - Hanudin Amin (Penerbit Universiti Kebangsaan Malaysia, 2012)
The paper tests the effects of attitude, subjective norm and amount of information on the Islamic insurance participation.Drawing upon the theory of reasoned action (TRA), this study proposes a model to examine the factors within the Islamic insurance participation context. The model is tested using survey data from 206 respondents.Importantly , the results suggest that attitude, subjective norm and amount of information provide the best fit to the data and are of value to be considered as the indispensable factors in determining the Islamic insurance participation. The findings of this study shed some light on the consumers acceptance level of an Islamic insurance. Its also provides valuable insights for takaful operator to manage the Islamic insurance services effectively. Limitations and future research directions are outlined.